The Prognostic Role of Neutrophil-to-Lymphocyte Ratio (NLR) in Testicular Germ Cell Tumor (GCT) - Saputra, Haviv Muris; Hakim, Lukman (Folia Medica Indonesiana, 2022)
Highlights: • Neutrophil to lymphocyte ratio (NLR) has been reported by several studies for its role as a biomarker in various diseases, however, the role of NLR in testicular GCT is still unclear. • The characteristics and responses of testicular GCT patients among Indonesian men show similarity to other reports worldwide. • As a parameter, NLR shows promise to be used as a potential biomarker for prognosis in testicular GCT. Abstract: The global incidence of testicular cancer is 1-2% from all cancers. The attempts to maintain high therapeutic rates while decreasing the treatment-related side effects and toxicity have become the current concern. However, the reports regarding testicular germ cell tumors (GCT) in Indonesia are limited. Thus, we aimed to evaluate the clinical characteristics of testicular GCT patients undergoing bleomycin, etoposide, and cisplatin (BEP) chemotherapy, as well as their chemotherapy response and side effects. We reported the data of patients with Testicular Germ Cell Tumor from January 2015 to December 2019. Several data were retrieved, including patient demographics, tumor characteristics, treatment, and prognosis outcome. A total of 67 patients with testicular germ cell tumors were included in this study. The mean age was 28.9 years old. The chemotherapy regimens used were four cycles of (BEP) in 36 patients (53.7%), followed by three cycles of BEP in 22 patients (32.8%). Patients with seminoma GCT mostly had a complete response (54.1%), whereas most patients with non-seminoma GCT had progressive disease (47.8%). The multiple logistic regression analysis showed that NLR and S staging were independently associated with the patient's response to chemotherapy (OR 2.14, 95% CI 1.22, 3.78, p <0.01,OR 9.43, 95% CI 1.81, 49.14, p < 0.01). The clinical characteristics and response of testicular GCT patients among Indonesian men showed similarity with the current worldwide data. The NLR could be used as a potential biomarker for prognosis.